A aula universitária: onde ficam professor e aluno (?) / The university class: where are the teacher and student (?) - Lopes, Bendita Donaciano; de Andrade, Fernanda Borges; Chaves, Naima de Paula Salgado (Ensino em Re-Vista, 2016)
.